Hydrogeochemical assessment of groundwater of Raipur city industrial area Chhattisgarh, India. Issue 1 (December 2020) - Singh, V; Khan, R; Gupta, U; Vishwakarma, N; Jhariya, D C
Abstract: The present study aims to assess the hydrogeochemistry of groundwater of the industrial area of Raipur. During the investigation, groundwater is found to be neutral to slightly alkaline, and it is suitable for drinking and domestic purposes. Calculation of various quality parameters such as soluble sodium percentage (SSP), sodium adsorption ratio (SAR), residual sodium carbonate (RSC), percentage of sodium (%Na), Kelley ratio (KI), magnesium ratio (MR) and Permeability Index (PI) reveals that this groundwater can also be used for irrigation as well. Similarly industrial parameters i.e., Corrosivity Ratio (CR), Ryznar Stability Index (RSI), and Langelier Saturation Index (LSI) are calculated, which indicates the non-corrosive nature of the groundwater in most of the study area.